RESPON TANAMAN SAWI HIJAU (BRASSICA JUNCEA L.) TERHADAP PEMBERIAN PUPUK ORGANIK DAN ANORGANIK DI KELURAHAN RURUKAN KECAMATAN TOMOHON TIMUR - Ngantung, Jeanete A.B.; Rondonuwu, Jenny J.; Kawulusan, Rafli I. (Universitas Sam Ratulangi, 2018)
ABSTRACT This study aims to determine the effect of which combination of fertilizer doses is best for the growth of Mustard Plant (Brassica juncea L.). And the research was conducted in Kelurahan Rurukan Tomohon Timur Subdistrict Tomohon City. Soil analysis was conducted in Soil Chemistry and Soil Fertility Department of Soil Agricultural Faculty of Sam Ratulangi University of Manado.This study used a Completely Randomized Design (RAL) consisting of 7 treatment combinations and repeated as many as 4 (four) times to obtain 28 pot experiments. Each pot of the experiment contains 5 kg of soil.The results showed that soil mixture with various combinations of fertilizers had a significant effect on the height of the green mustard plant, the number of leaves of green mustard greens, and the fresh weight of the green mustard plant.The best combination of soil mixture with Urea, Sp36, and Compost fertilizer is 0.5 gram / pot Urea, 0.375 gram / pot Sp36, and 50 gram / pot compost.Keywords: urea fertilizer, Sp36 fertilizer, compost fertilizer